Beyond cellular detoxification: a plethora of physiological roles for MDR transporter homologs in plants - Remy, Estelle; Duque, Paula (Frontiers in Physiology, 2014)
Higher plants possess a multitude of Multiple Drug Resistance (MDR) transporter homologs that group into three distinct and ubiquitous families—the ATP-Binding Cassette (ABC) superfamily, the Major Facilitator Superfamily (MFS), and the Multidrug And Toxic compound Extrusion (MATE) family. As in other organisms, such as fungi, mammals, and bacteria, MDR transporters make a primary contribution to cellular detoxification processes in plants, mainly through the extrusion of toxic compounds from the cell or their sequestration in the central vacuole. This review aims at summarizing the currently available information on the in vivo roles of MDR transporters in plant systems. Taken together, these data clearly indicate that the biological functions of ABC, MFS, and MATE carriers are not restricted to xenobiotic and metal detoxification. Importantly, the activity of plant MDR transporters also mediates biotic stress resistance and is instrumental in numerous physiological processes essential for optimal plant growth and development, including the regulation of ion homeostasis and polar transport of the phytohormone auxin.